Clinical Practice Guidelines for Acute Heart Failure Treatment - Leonardo Maikel Gómez Carcassés; Raiko Cruz Sosa; Francisco Jesús Valladares Carvajal; Juan José Navarro López; Víctor René Navarro Machado; Lázaro Enrique de la Cruz Avilés (Universidad de las Ciencias Médicas de Cienfuegos, 2020)
The clinical practice guidelines are the result of the compilation and evaluation of all the relevant evidence available, on a particular topic, with the aim of helping physicians select the best diagnostic and therapeutic strategy to apply to a patient suffering from a determined disease. This guide primarily addresses the diagnostic and therapeutic aspects of acute heart failure, which is defined as the rapid onset or worsening of symptoms or signs of heart failure. It is a life-threatening entity, which can be caused by a primary cardiac dysfunction or precipitated by extrinsic factors, usually leading to hospitalization of the patient. This guide is addressed to both specialists and residents of cardiology, internal medicine, intensive and emergency medicine, comprehensive general medicine, anesthesiology and resuscitation specialties, as well as medical students.